A gradient micromechanical model to explore flexoelectric copolymers via stochastic chain growth - Moreno Mateos, Miguel Angel (European Journal of Mechanics A-Solids, 2023)
Flexoelectric sensors respond with an electric polarization when they are subjected to inhomogeneous deformation. When these are based on polymeric materials, the electro-mechanical coupling relates to the loss of microstructural symmetries of the polar polymer chains. The object of this work is to explore the mechanisms that induce flexoelectricity in soft (co)polymers via a micromechanical model that explicitly considers the spatial composition distribution of polymer chains. To this end, we analyze the deformation of the Arruda–Boyce 8-chain cell under inhomogeneous deformation and its influence on the overall polarization resulting from the polar monomers. Cells with random-walk chains and tailored degree of entanglement feed Monte Carlo simulations to inform an effective chain dipole that drives the flexoelectric polarization. Homogeneous stretch/compression of the cell accompanying bending deformation reinforce the flexoelectric response. In addition, we focus on stochastic chain-growth processes and the insertion of different types of polar monomers within a same chain. Here, we introduce a model where reactivity ratios of real copolymerization reactions control the resulting flexoelectric coupling. Since the framework allows to relate the effective flexoelectric polarization to any structural isomer distribution, it is especially convenient to model copolymers. Overall, the model is proposed as a versatile framework to explore the intricacies of flexoelectric (co)polymers and to foster the design of flexoelectric devices from real manufacturing parameters.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Constitutive modeling; Curvature-induced polarization; Dielectric polymers; Flexoelectricity; Micromechanics; Non-centrosymmetry

A Note on Big Data and Value Creation - Moreno-Mateos, Miguel Angel; Carou, Diego (Machine Learning and Artificial Intelligence with Industrial Applications, 2022)

Autonomous Robots and CoBots - Moreno-Mateos, Miguel Angel; Carou, Diego; Davim, J. Paulo (Enabling Technologies for the Successful Deployment of Industry 4.0, 2020)
Automation was a milestone in manufacturing during the Third Industrial Revolution, where industrial robots meant the end of a wide variety of routine and monotonous tasks. However, little human-machine interaction was possible. In fact, robots where enclosed within security areas where they could operate preventing any potential human injury and according to a repetitive pattern. With the advent of Industry 4.0, state-of-the-art active security systems are enabling growing worker-robot collaboration, by which human flexibility and machine accuracy merge. Collaborative robots (CoBots) comprise this sort of technology. Boosted by the Internet of Things, Cloud Computing and Big Data, robots in modern manufacturing rely on improved customization, adaptability and quality. In order to explore the potential of this technology, this paper is structured as follows. First, a description of the technology behind modern manufacturing robots. Second, a historical background together with a strengths-weaknesses discussion. Third, a state of the art of current applications in industry and a list of alternatives in the market. Finally, a series of trends concerning the future of the manufacturing industry and existing enterprises that are supporting the change.<br

Configurational force method enables fracture assessment in soft materials - Moreno Mateos, Miguel Angel; Steinmann, Paul (Journal of the Mechanics and Physics of Solids, 2024)
Configurational mechanics offers a framework for quantifying the tendency of defects to alter the material configuration. When applied to fracture mechanics, configurational forces can be used to quantify the propensity of cracks to propagate. An alternative, well-established approach involves analytical solutions for crack tip displacement fields. However, these solutions typically apply to a limited range of constitutive behaviors and oftentimes to the linear small strain regime. The ease of calculating configurational forces in a numerical Finite Element implementation, along with their applicability to soft fracture at large strains, motivates the study of their performance as a standalone fracture framework. In contrast to the majority of works that remain theoretical and numerical, our study includes a robust experimental approach to configurational forces at finite strains. We report tensile experiments on a soft elastomer with pre-cuts ante fracture initiation. In a first attempt to approach the -integral via configurational forces, we explore the performance of the linear elastic fracture mechanics solutions on Pacman-shaped domains that reproduce the crack tip vicinity. Then, we implement the entire boundary value problem with three-dimensional simulations that replicate the empirical tensile deformation of the soft elastomer samples. Subsequently, the results are benchmarked against estimations of the -integral obtained through a bespoke finite strain analytical crack tip solution. With the successful validation of the configurational force method at finite strains, we aim to establish a pipeline for the calculation of configurational forces in a standalone manner and circumventing the need for close-form analytical solution
Keywords: Configurational mechanicsMaterial forcesSoft fractureFinite strainsNumerical methodsExperimental mechanics

Crosslinking degree variations enable programming and controlling soft fracture via sideways cracking - Moreno Mateos, Miguel Angel; Steinmann, Paul (npj Computational Materials, 2024)
Large deformations of soft materials are customarily associated with strong constitutive and geometrical nonlinearities that originate new modes of fracture. Some isotropic materials can develop strong fracture anisotropy, which manifests as modifications of the crack path. Sideways cracking occurs when the crack deviates to propagate in the loading direction, rather than perpendicular to it. This fracture mode results from higher resistance to propagation perpendicular to the principal stretch direction. It has been argued that such fracture anisotropy is related to deformation-induced anisotropy resulting from the microstructural stretching of polymer chains and, in strain-crystallizing elastomers, strain-induced crystallization mechanisms. However, the precise variation of the fracture behavior with the degree of crosslinking remains to be understood. Leveraging experiments and computational simulations, here we show that the tendency of a crack to propagate sideways in the two component Elastosil P7670 increases with the degree of crosslinking. We explore the mixing ratio for the synthesis of the elastomer that establishes the transition from forward to sideways fracturing. To assist the investigations, we construct a novel phase-field model for fracture where the critical energy release rate is directly related to the crosslinking degree. Our results demonstrate that fracture anisotropy can be modulated during the synthesis of the polymer. Then, we propose a roadmap with composite soft structures with low and highly crosslinked phases that allow for control over fracture, arresting and/or directing the fracture. The smart combination of the phases enables soft structures with enhanced fracture tolerance and reduced stiffness. By extending our computational framework as a virtual testbed, we capture the fracture performance of the composite samples and enable predictions based on more intricate composite unit cells. Overall, our work offers promising avenues for enhancing the fracture toughness of soft polymer

Effects of soft and hard magnetic particles on the mechanical performance of ultra-soft magnetorheological elastomers - Moreno Mateos, Miguel Angel; Lopez-Donaire, Maria Luisa; Mokarram, Hossain; Garcia-Gonzalez, Daniel (Smart Materials and Structures, 2022)
Magnetorheological elastomers (MREs) mechanically respond to external magnetic stimuli by changing their mechanical properties and/or changing their shape. Recent studies have shown the great potential of MREs when manufactured with an extremely soft matrix and soft-magnetic particles. Under the application of an external magnetic field, such MREs present significant mechanical stiffening, and when the magnetic field is off, they show a softer response, being these alternative states fully reversible. Although soft-magnetic particles are suitable for their high magnetic susceptibility, they require the magnetic actuation to remain constant in order to achieve the magneto-mechanical stiffening. Here, we present an alternative solution based on hard-magnetic MREs to provide stiffening responses that can be sustained along time without the need of keeping the external magnetic field on. To this end, we manufacture novel extremely soft hard-magnetic MREs (stiffness in the order of 1 kPa) and characterise them under magneto-mechanical shear and confined magnetic expansion deformation modes, providing a comparison framework with the soft-magnetic counterparts. The extremely soft nature of the matrix allows for easily activating the magneto-mechanical couplings under external magnetic actuation. In this regard, we provide a novel approach by setting the magnetic actuation below the fully magnetic saturating field. In addition, free deformation tests provide hints on the microstructural transmission of torques from the hard-magnetic particles to the viscoelastic matrix, resulting in macroscopic geometrical effects and intricate shape-morphing phenomena.
Created from Fastlane, Scopus look-up
Keywords: experimental characterisation; hard-magnetics MRE; magnetic properties; magneto-mechanics; magnetorheological elastomers (MREs); multifunctional materials

Electro-mechanical actuation modulates fracture performance of soft dielectric elastomers - Moreno Mateos, Miguel Angel; Mehnert, Markus; Steinmann, Paul (International Journal of Engineering Science, 2024)
Soft dielectric elastomers respond to electric stimuli by undergoing large deformations and changes in their material properties. The actuation with deformable electrodes attached to the material originates Coulomb and dipole forces that convert the electric field into a mechanical response. Applications at large deformations can entail crack onset and propagation. Within this context, the response of a soft polymer to an applied electric field may serve to influence the fracture behavior of such materials, potentially enhancing it. Here we explore the fracture performance of an ultra-soft dielectric elastomer. To do so, we conduct tensile tests while applying electrical actuation on samples with pre-cuts. Additionally, we examine the elastomer filled with piezoelectric BaTiO3 particles to ameliorate the fracture performance beyond the limits observed in the unfilled material. In conjunction with the experiments, we employ a bespoke fracture phase-field model to analyze the stress triaxiality near the crack tip. The results indicate that the electric actuation induces beneficial crack tip blunting and stress de-concentration, enhancing the fracture toughness up to a 125 % and delaying crack propagation. Our work provides a route for applications of soft dielectric elastomers that require improved fracture properties or, more broadly, the modulation of fracture behavior.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Configurational forces; Dielectric elastomers; Filled elastomers; Multifunctional materials; Phase-field modeling; Soft fracture

Experimental and numerical investigation of the photo-mechanical response of azobenzene filled soft elastomers, Part I: Experimental investigations - Mehnert, Markus; Moreno Mateos, Miguel Angel; Griwatz, Jan H.; Müsse, Silke; Wegner, Hermann A.; Steinmann, Paul (Extreme Mechanics Letters, 2024)
Photosensitive elastomers have the ability to undergo significant deformations upon the illumination by light of a specific wave length. Compared to other non-mechanical stimuli used in materials such as electro- or magneto-active polymers, light offers interesting advantages such as ultra high application speed and spatial precision. Moreover, as light powers and controls the movement of the material, the need for stiff wiring or external energy sources is eliminated. This becomes especially important in the design of miniature sized applications such as nano-scale robots. In the scope of the present work the conversion of photonic energy into a mechanical response originates from switching molecules embedded into a soft polymer matrix. Upon stimulation by UV-light, these molecules can switch from their stable trans - into a meta-stable cis-isomer, which induces a mechanical response on the macro scale. Depending on the experiment this can be visible as a deformation of the material or an increase in stiffness. This contribution presents the results of various mechanical and photo-mechanical experiments performed with the silicone Elastosil P 7670™ mixed with azobenzene molecules. These experiments are conducted in such a fashion that the obtained results are well suited for the identification of material parameters that arise from a photo-viscoelastic continuum modeling approach.<br
Keywords: Photo-sensitive materials; Soft elastomers; Photo-mechanics

Hard-magnetic phenomena enable autonomous self-healing elastomers - Garcia-Gonzalez, Daniel; Ter-Yesayants, Tigran; Moreno Mateos, Miguel Angel; Lopez-Donaire, Maria Luisa (Composites Part B-Engineering, 2023)
We propose a new concept of self-healing soft material that does not require external actuation to heal after rupture. This consists of a sticky and soft elastomeric matrix filled with hard-magnetic particles. When the material breaks into two or more parts and these are approached to each other, the magnetic particles with residual magnetisation interact closing the crack. Then, if new mechanical loading is applied, the composite acts as a continuum structure transmitting internal forces homogeneously until reaching a new failure strain threshold. We demonstrate this novel concept with experiments under tensile loading and with a magneto-mechanical constitutive model that explains the healing mechanisms. The results indicate that the proposed soft materials are able to, after several fracture cycles, sustain mechanical loading beyond 20 % strains without compromising the structural integrity. The healed material experiences no mechanical degradation during cyclic loading and healing cycles. Moreover, on its healed state, it can sustain higher stresses than the original material without residual magnetisation. We demonstrate that the strain at failure is determined by the combined effect of magnetic and adhesive contributions, which are modulated by the applied deformation rate. Furthermore, we reveal that the combination of soft and hard magnetic particles in a hybrid magnetorheological elastomer enables superior healing performance.
Created from Fastlane, Scopus look-up
Keywords: Magneto-mechanics; Magnetorheological elastomers (MREs); Multifunctional materials; Self-healing; Soft robotics

Hard magnetics in ultra-soft magnetorheological elastomers enhance fracture toughness and delay crack propagation - Moreno Mateos, Miguel Angel; Hossain, Mokarram; Steinmann, Paul; Garcia-Gonzalez, Daniel (Journal of the Mechanics and Physics of Solids, 2023)
Pre-existing flaws in highly stretchable elastomers trigger fracture under large deformations. For multifunctional materials, fracture mechanics may be influenced by additional physical phenomena. This work studies the implications of hard magnetics on the fracture behaviour of ultra-soft magnetorheological elastomers (MREs). We experimentally demonstrate that MREs with remanent magnetisation have up to a 50% higher fracture toughness than non pre-magnetised samples. Moreover, we report crack closure due to the magnetic field as a mechanism that delays the opening of cracks in pre-magnetised MREs. To overcome experimental limitations and provide further understanding, a phase-field model for the fracture of MREs is conceptualised. The numerical model incorporates magneto-mechanical coupling to demonstrate that the stress concentration at the crack tip is smaller when the MRE is pre-magnetised. Overall, this work unveils intriguing applications for functional actuators, with better fracture behaviour and potential better performance under cyclic loading.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Experimental mechanics; Hard magnetics; Multifunctional materials; Phase-field modelling; Soft fracture; Ultra-soft magnetorheological elastomers

Hybrid magnetorheological elastomers enable versatile soft actuators - Moreno Mateos, Miguel Angel; Hossain, Mokarram; Steinmann, Paul; Garcia-Gonzalez, Daniel (npj Computational Materials, 2022)
Recent advances in magnetorheological elastomers (MREs) have posed the question on whether the combination of both soft- and hard-magnetic particles may open new routes to design versatile multifunctional actuators. Here, we conceptualise ultra-soft hybrid MREs (≈1–10 kPa stiffness) combining experimental and computational approaches. First, a comprehensive experimental characterisation is performed. The results unravel that the magneto-mechanical performance of hybrid MREs can be optimised by selecting an adequate mixing ratio between particles. Then, a multi-physics computational framework provides insights into the synergistic magneto-mechanical interactions at the microscale. Soft particles amplify the magnetisation and hard particles contribute to torsional actuation. Our numerical results suggest that the effective response of hybrid MREs emerges from these intricate interactions. Overall, we uncover exciting possibilities to push the frontiers of MRE solutions. These are demonstrated by simulating a bimorph beam that provides actuation flexibility either enhancing mechanical bending or material stiffening, depending on the magnetic stimulation.
CRIS-Team Scopus Importer:2022-08-05

Influence of elastomeric matrix and particle volume fraction on the mechanical response of magneto-active polymers - Garcia-Gonzalez, Daniel; Moreno Mateos, Miguel Angel; Valencia, Leticia; Arias, Angel; Velasco, Diego (Composites Part B-Engineering, 2021)
Magneto-active polymers (MAPs) are revolutionising the fields of material science and solid mechanics as well as having an important presence in the bioengineering community. These composites consist of a polymeric matrix (i.e., elastomer) filled with magnetic particles (i.e., iron particles). When bonded together, these two phases form a continuum solid that, under the application of an external magnetic field, mechanically reacts leading to changes in shape and volume or/and alterations in its rheological properties. Such a magneto-mechanical response is determined by the material properties of the polymeric matrix and magnetic particles. In this work, we present the mechanical characterisation of MAPs constituted by PDMS filled with carbonyl iron powder (CIP) particles. To this end, sixteen different combinations of elastomeric base/crosslinker mixing ratio (from 5:1 to 20:1) and particles’ volume fraction (from 0% to 30%) are tested under tensile loading. These results are analysed and provide the bases for the formulation of a nonlinear constitutive model that accounts for these dependencies. The modelling approach is extended to incorporate magneto-mechanical effects. Finally, the complete model is used to provide theoretical guidance for magneto-active systems, highlighting potential applications in epithelial wound healing stimulation.
Created from Fastlane, Scopus look-up
Keywords: Constitutive modelling; Crosslinking; Magneto-active polymer (MAP); Magneto-mechanics; Mechanical characterisation; Multifunctional composites

Influence of magnetic boundary conditions on the quantitative modelling of magnetorheological elastomers - Moreno Mateos, Miguel Angel; Danas, Kostas; Garcia-Gonzalez, Daniel (Mechanics of Materials, 2023)
The complex magneto-mechanical coupling that governs the material response of magnetorheological elastomers (MREs) requires computational tools to assist the design process. Computational models are usually based on finite element frameworks that often simplify and idealise the magnetic source and the associated magnetic boundary conditions (BCs). However, these simplifications may lead to important disagreement between the actual material behaviour and the modelled one, even at the qualitative level. In this work, we provide a comprehensive study on the influence of magnetic BCs and demonstrate the importance of considering them in the overall material-structure modelling strategy. To this end, we implement a magneto-mechanical framework to model the response of soft- and hard-magnetic MREs under magnetic fields generated by an idealised far-field uniform magnetic source, a permanent magnet, a coil system, and an electromagnet with two iron poles. The results unveil remarkable heterogeneities in computed local magnetostriction and magnetic fields depending on the magnetic setup used. A detailed discussion based on material and structural contributions provides a robust, rigorous, and necessary modelling route for future works.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Boundary conditions; Computational mechanics; Magneto-mechanics; Magnetorheological elastomers; Magnetostriction

Insights into the viscohyperelastic response of soft magnetorheological elastomers: Competition of macrostructural versus microstructural players - Lucarini, Sergio; Moreno Mateos, Miguel Angel; Danas, Kostas; Garcia-Gonzalez, Daniel (International Journal of Solids and Structures, 2022)
Magnetorheological elastomers (MREs) are multifunctional composites that consist of an elastomeric matrix filled with magnetic particles. These materials respond to an external magnetic field by mechanically deforming and/or changing their magnetorheological properties. Such a multi-physical response has made them extraordinary candidates for a wide variety of applications in soft robotics and bioengineering. However, there are still some gaps of knowledge that prevent the optimal design and application of these MREs. In this regard, the effect of viscoelastic mechanisms remains elusive from a microstructural perspective. To the best of the authors’ knowledge, this work provides for the first time a numerical homogenization analysis for various magneto-active microstructures accounting for viscous deformation mechanisms. To this end, we propose an incremental variational formulation that incorporates viscoelasticity via internal variables, which is properly modified to deal with the continuity of Maxwell stresses. The proposed framework is applied to study the magneto-mechanical couplings in extremely soft MREs (stiffness < 10 kPa). Such a soft matrix promotes microstructural rearrangements while transmitting internal forces leading to macrostructural synergistic responses. The constitutive parameters are calibrated with experimental tests. The numerical results are accompanied with original magnetostriction tests considering different sample geometries and confined magneto-mechanical tests, reporting the macroscopic response. The results obtained in this work suggest that the effective magneto-mechanical response of the MRE is the outcome of a competition between macrostructural and local microstructural responses, where viscous mechanisms play a relevant role.
Created from Fastlane, Scopus look-up
Keywords: Constitutive modeling; Magnetorheological elastomer (MRE); Microstructural homogenization; Multifunctional composites; Viscoelasticity

Magneto-mechanical system to reproduce and quantify complex strain patterns in biological materials - Moreno Mateos, Miguel Angel; Gonzalez-Rico, Jorge; Nunez-Sardinha, Emanuel; Gomez-Cruz, Clara; Lopez-Donaire, Maria Luisa; Lucarini, Sergio; Arias, Angel; Muñoz-Barrutia, Arrate; Velasco, Diego; Garcia-Gonzalez, Daniel (Applied Materials Today, 2022)
Biological cells and tissues are continuously subjected to mechanical stress and strain cues from their surrounding substrate. How these forces modulate cell and tissue behavior is a major question in mechanobiology. To conduct studies under controlled varying physiological strain scenarios, a new virtually-assisted experimental system is proposed allowing for non-invasive and real-time control of complex deformation modes within the substrates. This approach is based on the use of extremely soft magneto-active polymers, which mimic the stiffness of biological materials. Thus, the system enables the untethered control of biological substrates providing reversible mechanical changes and controlling heterogeneous patterns. Motivated on a deep magneto-mechanical characterization across scales, a multi-physics and multi-scale in silico framework was developed to guide the experimental stimulation setup. The versatility and viability of the system have been demonstrated through its ability to reproduce complex mechanical scenarios simulating local strain patterns in brain tissue during a head impact, and its capability to transmit physiologically relevant mechanical forces to dermal fibroblasts. The proposed framework opens the way to understanding the mechanobiological processes that occur during complex and dynamic deformation states, e.g., in traumatic brain injury, pathological skin scarring or fibrotic heart remodeling during myocardial infarction.
Created from Fastlane, Scopus look-up
Keywords: Biomechanical stimulation; Computational modeling; Magneto-active materials; Mechanobiology; Multifunctional substrates

New experimental insights into magneto-mechanical rate dependences of magnetorheological elastomers - Moreno Mateos, Miguel Angel; Gonzalez-Rico, Jorge; Lopez-Donaire, Maria Luisa; Arias, Angel; Garcia-Gonzalez, Daniel (Composites Part B-Engineering, 2021)
Magnetorheological elastomers (MREs), consisting of an elastomeric matrix filled with magnetic particles, are one of the most promising multifunctional composites. The main advantage of these materials is their response to external magnetic fields by mechanically deforming and/or changing their magnetorheological properties. This multi-physical nature makes them ideal candidates for timely applications in soft robotics and bioengineering. Although several works have addressed the magneto-mechanical coupling in these composites from both experimental and modelling approaches, there is still a big gap of knowledge preventing the full understanding of their underlying physics. In this regard, there is no experimental work addressing a comprehensive magneto-mechanical characterisation combining different MRE configurations, mechanical deformation modes and magnetic conditions. Furthermore, the interplays of rate dependences into such magnetorheological behaviour still remain elusive. In this work, we provide an unprecedented experimental characterisation of a soft MRE considering more than 100 different experimental conditions involving more than 600 tests. The experiments include monotonous uniaxial compression at different deformation rates and magnetic conditions, magneto-mechanical DMA tests, relaxation tests, oscillatory shear tests at different deformation rates and magnetic conditions, magneto-mechanical shear frequency sweep tests, and novel magneto-mechanical experiments. The results obtained in this work provide full characterisation of soft MREs with a special focus on rate dependences, forming the basis to explain novel multifunctional mechanisms identified behind their coupled response. In addition, it opens the door to new constitutive and modelling approaches.
Created from Fastlane, Scopus look-up
Keywords: Experimental mechanics; Magneto-mechanical rheology; Magneto-rheological elastomers (MREs); Multifunctional composites; Smart materials; Viscoelasticity

Unveiling the blockchain potential for the future of manufacturing: A multipurpose blockchain network - Carou, Diego; Calles, Antonio Francisco; Moreno, Miguel Angel; Palacios, Alberto Miguel (Manufacturing in Digital Industries, 2020)
In the past decades, new technologies that relate to the Internet have been able to reshape the economy completely. Nowadays, blockchain technology is recognized as one of the new technologies with potential for completely transforming sectors such as banking. Nevertheless, the philosophy and basic principles in which the technology is developed may be applicable in other sectors such as manufacturing. Despite the technology is still immature, the technology can offer solutions to improving management and traceability in supply chains, fostering collaborative and open innovation, enhancing the use of certification, optimizing human resources management, developing improved R&D funding strategies and creating trust by means of online accounting. In this chapter, a multipurpose blockchain network is proposed to be used by all manufacturing actors involved in activities such as the aforementioned.
Created from Fastlane, Scopus look-up
Keywords: Blockchain; Certification; Industry 4.0; Manufacturing; Networks; Open innovation; R&D

Versatile data-adaptive hyperelastic energy functions for soft materials - Wiesheier, Simon; Moreno Mateos, Miguel Angel; Steinmann, Paul (Computer Methods in Applied Mechanics and Engineering, 2024)
Download full issue Search ScienceDirect Search ScienceDirect Outline Abstract Keywords 1. Introduction 2. Hyperelasticity based on a approximation of the strain energy function 3. Inverse identification of the parameters of the approximated strain energy function 4. Experimental insights: threefold application and validation of the model 5. Conclusion and outlook CRediT authorship contribution statement Declaration of competing interest Acknowledgment Appendix A. Normalized error plots of forces and vertical displacement fields Appendix B. Sensitivity matrix Data availability References Show full outline Figures (10) Fig. 1. Graphical comparison of linear basis functions (above, k=2) and cubic basis… Fig. 2. Sampled invariants Ī1 at the quadrature points (c) across all load steps of a… Fig. 3. Deformed samples featuring holes of different dimensions for three elastomers Fig. 4. Identification of the strain energy function W̄(I,Ī1) for the material… Fig. 5. Identification of the strain energy function W̄(I,Ī1) for the material DOWSIL Fig. 6. Identification of the strain energy function W̄(I,Ī1)+W̄(I,Ī2) for the… Show 4 more figures Elsevier Computer Methods in Applied Mechanics and Engineering Volume 430, 1 October 2024, 117208 Computer Methods in Applied Mechanics and Engineering Versatile data-adaptive hyperelastic energy functions for soft materials Author links open overlay panelSimon Wiesheier a, Miguel Angel Moreno-Mateos a, Paul Steinmann a b a Institute of Applied Mechanics, Friedrich-Alexander-Universität Erlangen–Nürnberg, Egerlandstr. 5, 91058, Erlangen, Germany b Glasgow Computational Engineering Centre, School of Engineering, University of Glasgow, G12 8QQ, United Kingdom Received 21 May 2024, Revised 25 June 2024, Accepted 30 June 2024, Available online 11 July 2024, Version of Record 11 July 2024. What do these dates mean? crossmark-logo Show less Add to Mendeley Share Cite https://doi.org/10.1016/j.cma.2024.117208 Get rights and content Under a Creative Commons license open access Abstract Applications of soft materials are customarily linked to complex deformation scenarios and material nonlinearities. In the bioengineering field, soft materials typically mimic the low stiffness of biological matter subjected to extreme deformations. Computational frameworks surge as a versatile tool to assist the design of functional applications. The constitutive model lies at the core of such frameworks. In this regard, the customary extreme non-linear behavior of elastomers poses an additional challenge to thoroughly capture the material behavior. Here, data-driven methodologies hold considerable promise for enhancing constitutive modeling when contrasted with phenomenological approaches. In this investigation, we introduce a versatile data-adaptive method tailored to the modeling of hyperelastic soft materials at finite strains. Specifically, our method substitutes an a priori chosen model for the strain energy function by a flexible interpolant defined on a discretized invariant space. Within this framework, the interpolation values assume the role of material parameters and are determined through finite element model updating to conform to measured experimental data — comprising full-field displacements coming from Digital-Image-Correlation and global reaction forces. We validate the method on uniaxial experimental tests of soft elastomers, encompassing , , and . Overall, we aim to establish a new route for the construction of hyperelastic energy functions, untethered from any predefined existing models or assumptions regarding the shape of the energ
Keywords: Data-driven; Parameter identification; Soft materials; Finite-element-method; Finite strains; Experimental mechanics